Adopting the eGameFlow Model in an Educational Game to Increase Knowledge about Vaccination - Mohd Johari, Nur Farahin; Muhammad Ridzuan L, Muhammad Amirul Naim; Ishak, Norshahidatul Hasana; Zaini, Hazrati (Society of Visual Informatics, 2023)
Vaccination is one preventive measure to prevent oneself from getting any diseases. Vaccinations work by training our immune system to produce antibodies and weaken the targeted disease. Unfortunately, the number of unvaccinated children has increased because some parents reject or doubt the effectiveness of vaccines. This skepticism could result in a resurgence of vaccine-preventable diseases. Additionally, some contribute to vaccine refusal due to other reasons like vaccine misinformation, religious convictions, and insufficient knowledge. The game aims to develop knowledge and awareness to enhance vaccine behavior and acceptance among individuals. eGameFlow model were used as the methodology for game development. This model was chosen as it focuses on the educational game environment, which addresses learning components in the game. There are eight criteria to be considered to evaluate enjoyment using this model. To measure the users’ enjoyment, a set of questionnaires adopted from the eGameFlow model has been used for the evaluation. It is created explicitly to measure learners’ enjoyment of e-Learning games. This game gathers positive feedback from 30 respondents and shows promising results to achieve the objective. All eGameFlow criteria were positive towards enjoyment, with knowledge improvement being the highest contributor. The overall average of the evaluation was at an agreeable level, with a score of 81%, considered as achieving the goal. For future enhancement in increasing player’s enjoyment and game effectiveness, the game can be created in 3D environment to provide deep immersion and autonomy to the player.